Calcium-magnesium double-site modified sodium electrode layered positive electrode material and preparation method thereof

By modifying the iron-manganese-based layered cathode material through dual-site doping with calcium/magnesium ions and precisely controlling the magnesium doping amount, the problem of harmful phase change of Fe/Mn-based cathode materials under high voltage is solved, and efficient and stable sodium storage performance and electrochemical performance are achieved, making it suitable for large-scale commercial production.

CN120709354APending Publication Date: 2025-09-26NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510971487.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing layered Fe/Mn-based cathode materials undergo harmful phase changes under high voltage, resulting in capacity decay and shortened cycle life. In addition, the relationship between the amount of magnesium ion doping and the P2/O3 dual-phase structure components lacks systematic clarification, which limits their application in sodium-ion batteries.

Method used

By modifying the iron-manganese-based layered cathode material through dual-site doping with calcium/magnesium ions, the amount of Mg2+ ion species is precisely set. Combined with component analysis and mathematical nonlinear fitting, fine regulation of the P2/O3 dual-phase structure is achieved, thereby improving the stability of the crystal structure and promoting efficient sodium ion transmission.

Benefits of technology

It achieves efficient and stable sodium storage performance, improves electrochemical performance and cycle life, and is suitable for large-scale commercial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120709354A_ABST
    Figure CN120709354A_ABST
Patent Text Reader

Abstract

The invention discloses a calcium-magnesium double-site modified sodium electric layered positive electrode material and a preparation method thereof, and belongs to the technical field of electrochemical energy storage. The chemical formula of the positive electrode material is Na < 0.67 > Ca Mn < 0.5 > Fe < 0.5-X > Mg < X > O < 2 >, Ca is doped at the Na position, and the doping amount a is equal to (0-0.04); mg is doped at a transition metal position, and the doping amount X is equal to (0-0.2); the preparation method comprises the following steps: (1) setting a magnesium doping amount X and a proportion Y of a P2 phase to an O3 phase to meet Y = e (0.00038196 + 1.35137 X-59.41639 X2), weighing raw materials according to a metal element molar ratio of n (Na): n (Ca): n (Mn): n (Fe): n (Mg) = 0.67: (0-0.04): 0.5: (0.5-0.3): X, and carrying out ball milling; and (2) tabletting the sample, calcining at high temperature, cooling, and regulating the X value to obtain the target positive electrode material. The iron-manganese-based layered positive electrode material is modified through calcium and magnesium ion double-site doping, the magnesium doping amount is precisely controlled, the relation between X and Y is established by combining component analysis and mathematical nonlinear fitting, double-phase fine regulation and control are achieved, the stability of a crystal structure is improved, efficient transmission of sodium ions is promoted, the process is simple, the cost is low, and the method is suitable for large-scale commercial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a calcium-magnesium dual-site modified sodium-electrode layered cathode material and a preparation method thereof. Background Art

[0002] Sodium-ion batteries (SIBs) are a promising new energy storage technology due to the widespread availability, abundant reserves, and low cost of their raw material, sodium. Developing SIBs with high capacity, high energy density, and long cycle life is currently a top priority, and new high-performance cathode materials are key to achieving these goals.

[0003] Layered Fe / Mn-based cathode materials have a relatively high capacity (approximately 10000 mAh g -1 ), low cost and easy preparation, and have attracted great attention, and have been widely studied and applied in the field of sodium-ion battery energy storage. However, its harmful phase transition under high voltage leads to a sharp decline in capacity, severely shortening the cycle life of the battery, which greatly limits its application in electrochemical energy storage. Doping modification, especially dual-site doping, is an effective strategy. Its advantages are particularly obvious when two doping ions act at different sites and produce effects that cannot be achieved by single-site doping through a synergistic effect. Therefore, the design of dual-site doping modification is crucial to improving the performance of layered Fe / Mn-based positive electrode materials.

[0004] Calcium is abundant in the earth's crust and relatively cheap, which helps reduce the production cost of cathode materials and makes them more economical in large-scale energy storage applications. 2+ Doping can improve the electronic and ionic conductivity of the material, thereby improving the rate performance. 2+ Doping can inhibit harmful phase transitions, such as the irreversible structural evolution of P2→O2, making the material more stable at high voltages and helping to maintain the long cycle life and high capacity retention of the battery. 2+ Because it has a similar radius to that of sodium ions (about 0.10nm vs. 0.12nm), it is often used for Na site doping modification. It can exert a pillar effect, inhibit high-pressure lattice oxygen loss, harmful phase transitions and volume changes, thereby ultimately optimizing the stability of the crystal structure and is expected to achieve high-efficiency and stable sodium storage performance.

[0005] Magnesium ions themselves have low toxicity and are relatively harmless to the environment and human health, meeting the requirements of green environmental protection. 2+It has a small ionic radius and a high charge density, and can enter the transition metal layer of the P2 structure iron-manganese-based positive electrode material, supporting and stabilizing the layered structure, reducing the structural collapse and phase transition of the material during the charge and discharge process, effectively inhibiting the migration of Fe / Mn ions, and maintaining the integrity of the electrode structure. At the same time, the study found that the additional introduction of magnesium ions in the transition metal site can induce the transformation of part of the P2 structure to the O3 structure, obtaining a P2 / O3 dual-phase structure material with stable structure and high specific capacity. This unique dual-phase structure can exert its anchoring effect under high voltage (>4.0V), effectively stabilizing the crystal structure in the deep insertion and extraction state, inhibiting harmful phase transitions, and maintaining its original structural integrity, which is particularly important for Fe / Mn-based layered oxides.

[0006] Compared with other doping ions (such as copper, nickel, etc.), the non-toxicity of calcium / magnesium ions makes them relatively harmless to the environment and human health, and meets the requirements of green environmental protection. Compared with nickel, its stability during the use of the battery helps to reduce the risk of safety problems such as thermal runaway in the battery and improve the safety of the battery. Secondly, calcium / magnesium ions can be more evenly distributed in the material, effectively avoiding the problem of copper ions easily forming clusters on the surface of the material, which leads to uneven electrode surface, thereby achieving better overall performance improvement. It is worth mentioning that the P2 / O3 dual-phase structure ratio is closely related to the electrochemical properties of Fe / Mn-based layered oxides and the sodium ion diffusion efficiency. How to achieve a controllable design of the P2 / O3 dual-phase structure ratio in order to maximize its anchoring effect is a top priority.

[0007] Studies have shown that the introduction of magnesium dopants during the synthesis process can induce a partial conversion of the P2 phase to the O3 phase, thereby yielding a P2 / O3 dual-phase material with both structural stability and high specific capacity. However, this mechanism has not been fully investigated in Fe / Mn-based cathode materials, and a systematic formula still lacks a quantitative formula for the quantitative evolution of the relationship between the magnesium ion doping level and the P2 / O3 dual-phase structure components. Exploring the synergistic effects of calcium / magnesium ion dual-site doping and P2 / O3 dual-phase structure design for high-performance sodium ion storage is of great strategic significance. Summary of the Invention

[0008] In view of the above-mentioned deficiencies in the prior art, the present invention provides a calcium-magnesium dual-site modified sodium layered cathode material and a preparation method thereof. The present invention modifies the iron-manganese-based layered cathode material by calcium / magnesium ion dual-site doping, and precisely sets the Mg 2+ The amount of ionic substances (0-0.2) is used to finely control the magnesium doping amount. Combined with component analysis and mathematical nonlinear fitting, its relationship with the ratio of the P2 / O3 dual-phase structure is explored to achieve fine dual-phase control, improve the stability of the crystal structure and promote the efficient transmission of sodium ions.

[0009] The specific technical solutions of the present invention are as follows:

[0010] The present invention provides a sodium-electrode layered cathode material modified with calcium and magnesium at two sites. The chemical formula of the cathode material is Na 0.67 Ca a Mn 0.5 Fe 0.5-X Mg X O2, wherein Ca doping is located at the Na position, and the doping amount is a = (0-0.04); Mg doping is located at the transition metal position, and the doping amount is X = (0-0.2), and a P2 / O3 dual-phase structure is formed by calcium-magnesium dual-site doping; the molar ratio of the metal elements is specifically: n(Na):n(Ca):n(Mn):n(Fe):n(Mg) = 0.67:(0-0.04):0.5:(0.5-0.3):(0-0.2).

[0011] Furthermore, the positive electrode material achieves dual optimization modification of calcium / magnesium ion synergistic regulation of layered iron-manganese positive electrode materials.

[0012] Furthermore, the positive electrode material is used as a working positive electrode material in a sodium ion battery to achieve efficient and stable sodium storage.

[0013] Furthermore, in the electrochemical performance test of the positive electrode material, the following method was adopted: an Fe / Mn-based material with dual-site doping of calcium / magnesium ions and synergistic modification of a P2 / O3 dual-phase structure was used as the positive electrode, sodium metal was used as the counter electrode, and a 1.0M NaClO4 PC / EC (1:1) solution (containing 5% FEC) was used as the electrolyte to assemble a half-cell system.

[0014] The present invention also provides a method for preparing a calcium-magnesium dual-site modified sodium-electrode layered cathode material, comprising the following steps:

[0015] Step S1: Set the magnesium doping amount to X, and the ratio of the P2 phase to the O3 phase in the positive electrode material to be prepared to Y, where Y and X satisfy the functional relationship: Weigh the raw materials according to the metal element molar ratio n(Na):n(Ca):n(Mn):n(Fe):n(Mg)=0.67:(0-0.04):0.5:(0.5-0.3):X and perform ball milling;

[0016] Step S2: The sample obtained after ball milling is pressed into a tablet, calcined at high temperature, and then cooled. The P2 / O3 dual-phase ratio is controlled by adjusting the amount of magnesium dopant substance, and finally a calcium / magnesium dual-site modified sodium electrode layered positive electrode material with a target P2 / O3 dual-phase ratio is obtained.

[0017] Preferably, the raw materials in step S1 include: the sodium source is sodium carbonate, the manganese source is manganese oxide, the iron source is iron oxide, the calcium source is calcium carbonate, and the magnesium source is magnesium oxide.

[0018] Preferably, the amount of sodium carbonate in the raw material in step S1 is 5% excess relative to the stoichiometric ratio.

[0019] Preferably, the ball milling in step S1 uses anhydrous ethanol as the medium, the ball milling time is 6-12 hours, and the material-to-ball ratio is 1:(5-10).

[0020] Preferably, in step S2, the calcination atmosphere is air, the calcination temperature is 800-1000° C., the calcination time is 8-16 h, and the heating rate is 5-10° C. / min.

[0021] Furthermore, the calcination temperature in step S2 is a key factor in crystal growth: too low a temperature will result in incomplete reaction or incomplete growth, while too high a temperature will increase energy consumption and cause excessive crystal growth. The calcination time is also critical: too short a time will result in insufficient reaction or insufficient grain growth, while too long a time will lead to excessive grain growth, causing agglomeration and hindering ion or charge transport.

[0022] Furthermore, the specific steps of controlling the P2 / O3 dual-phase ratio in step S2 are: using magnesium oxide as a dopant, accurately setting the Mg 2+ The amount of the ionic substance is X=(0-0.2), and the target product is obtained through ball milling and calcination processes.

[0023] Furthermore, the preparation method achieves dual optimization modification of calcium / magnesium ion dual-site doping and P2 / O3 dual-phase structure refinement and regulation of the layered iron-manganese positive electrode material.

[0024] The present invention further provides a sodium ion battery with efficient and stable sodium storage performance, comprising the positive electrode material.

[0025] The present invention further provides a method for regulating Na 0.67 Ca a Mn 0.5 Fe 0.5-X Mg X The method of the P2 / O3 dual-phase ratio of the O2 positive electrode material is to set the ratio of the P2 phase to the O3 phase in the positive electrode material to be prepared to Y, the magnesium doping amount to X, and Y and X to satisfy the functional relationship: The P2 / O3 dual-phase ratio Y is controlled by adjusting the amount X of the magnesium dopant substance.

[0026] Preferably, the regulation of Na 0.67 Ca a Mn 0.5 Fe 0.5-X Mg X In the method of P2 / O3 dual-phase ratio of O2 positive electrode material, a=(0-0.04), X=(0-0.2).

[0027] The beneficial technical effects of the present invention are:

[0028] (1) This invention differs from conventional Fe / Mn-based cathode modification methods in that it primarily achieves fine-tuning of the P2 / O3 dual-phase structure by regulating the magnesium ion doping level, thereby improving sodium ion transport efficiency and enhancing electrochemical performance. This invention establishes a functional relationship between the magnesium ion doping level and the component ratios of the P2 / O3 dual-phase structure, and evaluates the evolution of the P2 / O3 dual-phase structure at different ratios.

[0029] (2) The present invention adopts Na to Ca 2+ Doping optimization modification eliminates high-voltage lattice oxygen loss, improves crystal structure stability, and improves electrical properties.

[0030] (3) The present invention adopts calcium / magnesium ion dual-site doping to modify the iron-manganese-based layered positive electrode material to improve the crystal structure stability of the positive electrode material and promote the efficient transmission of sodium ions; it cleverly combines doping modification, P2 / O3 dual-phase engineering and electrochemical performance, and has great application potential; it has a high reproducibility and a simple preparation process, and is suitable for large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 XRD patterns of the Fe / Mn cathode materials prepared in Examples 1-5;

[0032] Figure 2 The two-phase ratio fitting curve of the Fe / Mn positive electrode material prepared in Examples 1-5;

[0033] Figure 3 0.1C first cycle charge-discharge curve of the Fe / Mn cathode material prepared in Example 1-5;

[0034] Figure 4 SEM analysis of the Fe / Mn cathode material prepared in Example 3;

[0035] Figure 5 EIS analysis of the Fe / Mn cathode materials prepared in Examples 1 and 3;

[0036] Figure 6 0.5C cycle performance test of the Fe / Mn positive electrode materials prepared in Examples 1 and 3 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0037] The present invention is described in detail below with reference to the accompanying drawings and embodiments. It is apparent that the embodiments described are only a portion of the embodiments of the present invention, rather than all of them. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are intended to fall within the scope of protection of the present invention.

[0038] In the following examples, half-cell systems were assembled using the dual-modified Fe / Mn-based cathode material obtained in this invention as the working electrode, sodium metal as the counter electrode, and a 1.0 M NaClO₄ solution in PC / EC (1:1) (containing 5% FEC) as the electrolyte to measure electrochemical performance. All other raw materials and processing techniques not otherwise specified are commercially available products or conventional techniques in the art.

[0039] The chemical formula of the target system is: Na 0.67 Ca a Mn 0.5 Fe 0.5-X Mg X O2, wherein Ca doping is located at the Na position, and the doping amount is 0-0.04; Mg doping is located at the transition metal position, and the doping amount is 0-0.2; the molar ratio of metal elements is: n(Na):n(Ca):n(Mn):n(Fe):n(Mg)=0.67:(0-0.04):0.5:(0.5-0.3):(0-0.2).

[0040] Example 1:

[0041] (1) Without calcium and magnesium doping (i.e., the calcium and magnesium doping amounts a and X were both 0), sodium carbonate, manganese oxide, and iron oxide were weighed according to the metal element molar ratio of n(Na):n(Ca):n(Mn):n(Fe):n(Mg) = 0.67:0:0.5:0.5:0, with the amount of sodium carbonate being 5% excess relative to the stoichiometric ratio. The mixture was ball-milled in ethanol for 6 h to achieve thorough mixing, with a material-to-ball ratio of 1:5.

[0042] (2) The ball-milled sample was placed in air atmosphere for high-temperature calcination: the calcination temperature was 900°C, the calcination time was 12 h, and the heating rate was 5°C / min;

[0043] (3) cooling the calcined sample to room temperature to obtain a positive electrode material;

[0044] (4) The obtained Fe / Mn-based cathode material has a P2 / O3 dual-phase structure ratio (P2:O3) of Y, which satisfies the following relationship with the magnesium doping amount X: When X=0, Y=1.

[0045] The specific steps for biphasic ratio verification are as follows: Figure 1The X-ray diffraction (XRD) pattern of Example 1 shows that the diffraction peaks are all indexed to a hexagonal layered structure of the P63 / mmc space group (PDF#54-0894), and no impurity peaks appear, indicating that the undoped sample of Example 1 has a P2 structure; the XRD data of Example 1 were refined using Fullprof software to further obtain information on the ratio of P2 and O3: when the magnesium ion doping amount X=0, the P2 / O3 structural component ratio (P2:O3) is 1.

[0046] (5) Using a blue electric test system and an electrochemical workstation, the Fe / Mn-based cathode material prepared above with a Ca / Mg dual-site doping and a P2 / O3 dual-phase structure was assembled into a half-cell; sodium metal was used as the counter electrode and a 1.0 M NaClO4 PC / EC (1:1) solution (containing 5% FEC) was used as the electrolyte to assemble the half-cell to measure its electrochemical performance.

[0047] Example 2:

[0048] (1) Using magnesium oxide as a dopant, accurately set the Mg 2+ The amount of ionic substance X = 0.05. Sodium carbonate, manganese oxide, iron oxide, calcium carbonate, and magnesium oxide are weighed according to the metal element molar ratio of n(Na):n(Ca):n(Mn):n(Fe):n(Mg) = 0.67:0.01:0.5:0.45:0.05, with the sodium carbonate used in a 5% excess relative to the stoichiometric ratio. Ball mill the mixture for 6 hours in ethanol to achieve thorough mixing, achieving a material-to-ball ratio of 1:5.

[0049] (2) The ball-milled sample was placed in air atmosphere for high-temperature calcination: the calcination temperature was 900°C, the calcination time was 12 h, and the heating rate was 5°C / min;

[0050] (3) cooling the calcined sample to room temperature to obtain a positive electrode material;

[0051] (4) The obtained Fe / Mn-based cathode material has a P2 / O3 dual-phase structure ratio (P2:O3) of Y, which satisfies the following relationship with the magnesium doping amount X: When X=0.05, Y=0.928.

[0052] The specific steps for biphasic ratio verification are as follows: Figure 1The X-ray diffraction (XRD) pattern of Example 2 shows diffraction peaks that can be indexed as a hexagonal layered structure of the P63 / mmc space group (PDF#54-0894) and a hexagonal layered structure of the Rmm space group (PDF#53-0349), and no impurity peaks appear, indicating that the magnesium doping of Example 2 successfully induced the formation of a P2 / O3 dual-phase structure. The XRD data of Example 2 were refined using Fullprof software to further obtain information on the ratio of P2 and O3. When the magnesium ion doping amount X=0.05, the P2 / O3 dual-phase structure component ratio (P2:O3) was 0.928.

[0053] (5) Using a blue electric test system and an electrochemical workstation, the Fe / Mn-based cathode material prepared above with a Ca / Mg dual-site doping and a P2 / O3 dual-phase structure was assembled into a half-cell; sodium metal was used as the counter electrode and a 1.0 M NaClO4 PC / EC (1:1) solution (containing 5% FEC) was used as the electrolyte to assemble the half-cell to measure its electrochemical performance.

[0054] Example 3:

[0055] (1) Using magnesium oxide as a dopant, accurately set the Mg 2+ The amount of ionic substance X = 0.1. Sodium carbonate, manganese oxide, iron oxide, calcium carbonate, and magnesium oxide are weighed according to the metal element molar ratio n(Na):n(Ca):n(Mn):n(Fe):n(Mg) = 0.67:0.02:0.5:0.4:0.1, with the sodium carbonate used in a 5% excess relative to the stoichiometric ratio. Ball mill the mixture for 6 hours in ethanol to achieve thorough mixing. The material-to-ball ratio is 1:10.

[0056] (2) The ball-milled sample was placed in air atmosphere for high-temperature calcination: the calcination temperature was 900°C, the calcination time was 12 h, and the heating rate was 5°C / min;

[0057] (3) cooling the calcined sample to room temperature to obtain a positive electrode material;

[0058] (4) The obtained Fe / Mn-based cathode material has a P2 / O3 dual-phase structure ratio (P2:O3) of Y, which satisfies the following relationship with the magnesium doping amount X: When X=0.1, Y=0.612.

[0059] The specific steps for biphasic ratio verification are as follows: Figure 1The X-ray diffraction (XRD) pattern of Example 3 shows diffraction peaks that can be indexed as a hexagonal layered structure of the P63 / mmc space group (PDF#54-0894) and a hexagonal layered structure of the Rmm space group (PDF#53-0349), and no impurity peaks appear, indicating that the magnesium doping of Example 3 successfully induces the formation of a P2 / O3 dual-phase structure. The XRD data of Example 3 were refined using Fullprof software to further obtain information on the ratio of P2 and O3: when the magnesium ion doping amount X=0.1, the P2 / O3 dual-phase structure component ratio (P2:O3) was 0.612.

[0060] (5) Using a blue electric test system and an electrochemical workstation, the Fe / Mn-based cathode material prepared above with a Ca / Mg dual-site doping and a P2 / O3 dual-phase structure was assembled into a half-cell; sodium metal was used as the counter electrode and a 1.0 M NaClO4 PC / EC (1:1) solution (containing 5% FEC) was used as the electrolyte to assemble the half-cell to measure its electrochemical performance.

[0061] Example 4:

[0062] (1) Using magnesium oxide as a dopant, accurately set the Mg 2+ The amount of ionic substance X = 0.15. Sodium carbonate, manganese oxide, iron oxide, calcium carbonate, and magnesium oxide are weighed according to the metal element molar ratio of n(Na):n(Ca):n(Mn):n(Fe):n(Mg) = 0.67:0.03:0.5:0.35:0.15, with the sodium carbonate used in a 5% excess relative to the stoichiometric ratio. Ball milling is performed in ethanol for 12 hours to achieve thorough mixing, with a material-to-ball ratio of 1:10.

[0063] (2) The ball-milled sample was placed in air atmosphere for high-temperature calcination: the calcination temperature was 800°C, the calcination time was 8 h, and the heating rate was 10°C / min;

[0064] (3) cooling the calcined sample to room temperature to obtain a positive electrode material;

[0065] (4) The obtained Fe / Mn-based cathode material has a P2 / O3 dual-phase structure ratio (P2:O3) of Y, which satisfies the following relationship with the magnesium doping amount X: When X=0.15, Y=0.359.

[0066] The specific steps for biphasic ratio verification are as follows: Figure 1The X-ray diffraction (XRD) pattern of Example 4 shows diffraction peaks that can be indexed as a hexagonal layered structure of the P63 / mmc space group (PDF#54-0894) and a hexagonal layered structure of the Rmm space group (PDF#53-0349), and no impurity peaks appear, indicating that the magnesium doping of Example 4 successfully induces the formation of a P2 / O3 dual-phase structure. The XRD data of Example 4 were refined using Fullprof software to further obtain information on the ratio of P2 and O3: when the magnesium ion doping amount X=0.15, the P2 / O3 dual-phase structure component ratio (P2:O3) was 0.359.

[0067] (5) Using a blue electric test system and an electrochemical workstation, the Fe / Mn-based cathode material prepared above with a Ca / Mg dual-site doping and a P2 / O3 dual-phase structure was assembled into a half-cell; sodium metal was used as the counter electrode and a 1.0 M NaClO4 PC / EC (1:1) solution (containing 5% FEC) was used as the electrolyte to assemble the half-cell to measure its electrochemical performance.

[0068] Example 5:

[0069] (1) Using magnesium oxide as a dopant, accurately set the Mg 2+ The amount of ionic substance, X, is 0.2. Sodium carbonate, manganese oxide, iron oxide, calcium carbonate, and magnesium oxide are weighed according to the molar ratio of the metal elements n(Na):n(Ca):n(Mn):n(Fe):n(Mg) = 0.67:0.04:0.5:0.3:0.2, with sodium carbonate in 5% excess relative to the stoichiometric ratio. Ball milling is performed in ethanol for 8 hours to achieve thorough mixing, with a material-to-ball ratio of 1:10.

[0070] (2) The ball-milled sample was placed in air atmosphere for high-temperature calcination: the calcination temperature was 1000°C, the calcination time was 16 h, and the heating rate was 10°C / min;

[0071] (3) cooling the calcined sample to room temperature to obtain a positive electrode material;

[0072] (4) The obtained Fe / Mn-based cathode material has a P2 / O3 dual-phase structure ratio (P2:O3) of Y, which satisfies the following relationship with the magnesium doping amount X: When X=0.2, Y=0.090.

[0073] The specific steps for biphasic ratio verification are as follows: Figure 1The X-ray diffraction (XRD) pattern of Example 5 shows diffraction peaks that can be indexed as a hexagonal layered structure of the P63 / mmc space group (PDF#54-0894) and a hexagonal layered structure of the Rmm space group (PDF#53-0349), and no impurity peaks appear, indicating that the magnesium doping of Example 5 successfully induced the formation of a P2 / O3 dual-phase structure. The XRD data of Example 5 were refined using Fullprof software to further obtain information on the ratio of P2 and O3. When the magnesium ion doping amount X=0.2, the P2 / O3 dual-phase structure component ratio (P2:O3) was 0.090.

[0074] (5) Using a blue electric test system and an electrochemical workstation, the Fe / Mn-based cathode material prepared above with a Ca / Mg dual-site doping and a P2 / O3 dual-phase structure was assembled into a half-cell; sodium metal was used as the counter electrode and a 1.0 M NaClO4 PC / EC (1:1) solution (containing 5% FEC) was used as the electrolyte to assemble the half-cell to measure its electrochemical performance.

[0075] Comparative Example 1

[0076] Based on Example 3, no calcium doping was performed, and Mg was precisely introduced only at the transition metal position. 2+ ions (doping amount X = 0.2), and the same method was used to measure its electrochemical properties.

[0077] Comparative Example 2

[0078] Based on Example 3, no magnesium doping was performed, and Ca was introduced only at the sodium position. 2+ ions (doping amount is 0.02), and the same method was used to measure its electrochemical properties.

[0079] Test example:

[0080] 1. Summary of the characteristics of the two-phase structure:

[0081] like Figure 1 As described above, magnesium doping successfully induced the formation of a P2 / O3 dual-phase structure, and the P2 / O3 dual-phase structure component ratios of the materials of Examples 1-5 were finally obtained through XRD refinement (as shown in Table 1). Table 1 summarizes the P2 / O3 ratios obtained through refinement of Examples 1-5. The errors (Rwp) of the refinement results are all less than 10%, indicating that the structural model is in good agreement with the experimental data. The function parameters (a = 3.8196×10 -4 , b=1.35137,c=-59.41639) and Figure 2 The fitting curve (R 2 =0.99518, R 2The coefficient of determination ranges from 0 to 1, where 1 represents a perfect fit of the model to the data. It is verified that when the magnesium doping level varies from 0 to 0.2, the P2 / O3 dual-phase ratio is highly consistent with the mathematical model. The model achieved high-precision fitting based on the five groups of data points (XY values) of Examples 1-5, indicating that the fitting results are reasonable.

[0082] Table 1 Analysis of magnesium ion doping amount-P2 / O3 dual-phase structure components

[0083]

[0084]

[0085] Table 2 Parameters of the relationship between magnesium ion doping amount and P2 / O3 dual-phase structure function

[0086]

[0087] The above results further indicate that the P2 / O3 dual-phase structure ratio can be optimized by finely controlling the magnesium doping amount (X=0-0.2); in particular, Example 3 (X=0.1) achieves an equal-proportion P2 / O3 dual-phase structure, which is conducive to maximizing its unique anchoring effect, and provides a quantitative basis for the controllable design of the P2 / O3 dual-phase ratio.

[0088] 2. Electrical performance test:

[0089] like Figure 3 The 0.1C first cycle charge and discharge curves of the Fe / Mn positive electrode materials prepared in Examples 1-5 are shown in the figure. The initial discharge specific capacity of the sample in Example 1 is 189.4 mAh / g, the initial discharge specific capacity of the sample in Example 2 is 180.2 mAh / g, the initial discharge specific capacity of the sample in Example 3 is 172.7 mAh / g, the initial discharge specific capacity of the sample in Example 4 is 165.2 mAh / g, and the initial discharge specific capacity of the sample in Example 5 is 157.7 mAh / g. Among them, the initial discharge specific capacity performance of the sample in Example 1 is the best. The reason is that both Ca and Mg are inert elements. As the doping amount increases (such as in Examples 2-5), the capacity also decreases slightly.

[0090] Figure 3The first-cycle discharge capacity of Examples 1-5 (189.4, 180.2, 172.7, 165.2, 157.7 mAh / g) is clearly correlated with the magnesium doping amount (0, 0.05, 0.1, 0.15, 0.2) and the P2 / O3 dual-phase ratio (1.0, 0.928, 0.612, 0.359, 0.090) in Table 1: as the magnesium doping amount increases, the material capacity decreases step-by-step, and the proportion of the P2 phase continues to decrease, which confirms that the occupation of active sites by inactive magnesium ions will weaken the capacity, but lays the foundation for the regulation of the dual-phase structure.

[0091] Figure 4 This is an SEM image of the Fe / Mn positive electrode material prepared in Example 3. The results show that the sample in Example 3 presents the morphological characteristics of "irregular particles with relatively uniform distribution", indicating that the dual modification strategy is conducive to forming small and uniform particles and increasing the specific surface area of ​​the positive electrode material.

[0092] Figure 5 The EIS spectra of Example 1 and Example 3 show that: R ct is 416.8Ω, and the R ct is 248.1Ω. Therefore, the R ct The impedance performance of the sample of Example 3 is improved by about 40% compared with the sample of Example 1.

[0093] Figure 6 The 0.5C cycle performance of the Fe / Mn positive electrode materials prepared in Examples 1 and 3 and Comparative Examples 1 and 2, the data show that: at a rate of 0.5C, the first-cycle discharge specific capacities of Example 1, Example 3, Comparative Example 1 and Comparative Example 2 are 146.1mAh / g, 122.9mAh / g, 127.7mAh / g and 137.2mAh / g, respectively. After 100 cycles, the discharge specific capacities are 67.7mAh / g, 107.8mAh / g, 88.23mAh / g and 105.0mAh / g, respectively, and the capacity retention rates are 46.3%, 87.7%, 69.1% and 76.5%, respectively. Compared with the sample in Example 1, the cycle performance (in terms of capacity retention rate) of the sample in Example 3 is improved by 41.4 percentage points (the improvement rate is 89.4%). It can be judged from this that the electrochemical performance of Example 3 is the best. This result further shows that in Example 3, by precisely controlling the Mg 2+ The equal-proportional P2 / O3 dual-phase structure obtained by the amount of ionic species (X=0.1) can maximize its unique anchoring effect, and combined with the pillaring effect of calcium ions, it has significant advantages in improving the structural stability of the positive electrode material.

[0094] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A calcium-magnesium dual-site modified sodium-electrode layered cathode material, characterized in that: The chemical formula of the positive electrode material is Na 0.67 Ca a Mn 0.5 Fe 0.5-X Mg X O2, wherein Ca doping is located at the Na position, and the doping amount is a = (0-0.04); Mg doping is located at the transition metal position, and the doping amount is X = (0-0.2), and a P2 / O3 dual-phase structure is formed by calcium-magnesium dual-site doping; the molar ratio of the metal elements is specifically: n(Na):n(Ca):n(Mn):n(Fe):n(Mg) = 0.67:(0-0.04):0.5:(0.5-0.3):(0-0.2).

2. The method for preparing the calcium-magnesium dual-site modified sodium-electrode layered cathode material according to claim 1, characterized in that: The following steps are involved: Step S1: Set the magnesium doping amount to X, and the ratio of P2 phase to O3 phase in the positive electrode material to be prepared to Y, where Y and X satisfy the functional relationship: Y = e (0.00038196+1.35137X-59.41639X2) , weigh the raw materials according to the metal element molar ratio n(Na):n(Ca):n(Mn):n(Fe):n(Mg)=0.67:(0-0.04):0.5:(0.5-0.3):X, and perform ball milling; Step S2: The sample obtained after ball milling is pressed into a tablet, calcined at high temperature, and then cooled. The P2 / O3 dual-phase ratio is controlled by adjusting the amount of magnesium dopant substance, and finally a calcium / magnesium dual-site modified sodium electrode layered positive electrode material with a target P2 / O3 dual-phase ratio is obtained.

3. The preparation method according to claim 2, characterized in that The raw materials in step S1 include: a sodium source of sodium carbonate, a manganese source of manganese oxide, an iron source of iron oxide, a calcium source of calcium carbonate, and a magnesium source of magnesium oxide.

4. The preparation method according to claim 3, characterized in that The amount of sodium carbonate in the raw material in step S1 is 5% excess relative to the stoichiometric ratio.

5. The preparation method according to claim 2, characterized in that The ball milling in step S1 uses anhydrous ethanol as the medium, the ball milling time is 6-12 hours, and the material-to-ball ratio is 1:(5-10).

6. The preparation method according to claim 2, characterized in that In step S2, the calcination atmosphere is air, the calcination temperature is 800-1000° C., the calcination time is 8-16 hours, and the heating rate is 5-10° C. / min.

7. A sodium ion battery with efficient and stable sodium storage performance, characterized in that: Comprising the positive electrode material according to any one of claims 1 to 6.

8. A method for regulating Na 0.67 Ca a Mn 0.5 Fe 0.5-X Mg X The method of P2 / O3 dual phase ratio of O2 positive electrode material is characterized in that Set the ratio of P2 phase to O3 phase in the cathode material to be prepared to Y, the magnesium doping amount to X, and Y and X satisfy the functional relationship: Y = e (0.00038196+1.35137X-59.41639X2) By adjusting the amount X of the magnesium dopant substance, the P2 / O3 dual-phase ratio Y can be controlled.

9. The method according to claim 8, characterized in that a=(0-0.04), X=(0-0.2).